OPPORTUNITIES TO OBTAIN MEAT FROM DOMESTIC COWS: EASTERN ANATOLIAN RED CATTLE EXAMPLE IN TURKEY - Yüksel, Sadrettin (Journal of Agricultural Sciences (Belgrade), 2021)
Breeding model formation is under the impact of the rearing systems and environment conditions in the region where the activity is carried out. The aim of this research is to evaluate the current situation and create a model for the some places that make animal production based on social and cultural values in world. For this aim was decided on Eastern Anatolian Red (EAR) breed that adapted to arid and barren areas, in Turkey. The animal material of research comprised 31 head EAR cows including different ages, fed in pasture and barn. In study was determined the impact on some carcass characteristics for meat production of factors such as age, birth weight and milk suction time. The animals were divided into 6 groups due to birth weight to 4 groups due to age and 6 groups due to milk suction time. They were reared under a conventional system that was based on pasture during summer and semi-intensively during winter. The effect of the age group on carcass length, fat thickness over LD, marbling score, and Load Distribution Ratio (LDR) was significant (P< 0.05). Significant (P< 0.05) differences were noted for carcass length, fat thickness over LD, and marbling score among treatment groups in terms of birth weight. Milk suction time had a significant (P< 0.05) effect on all the parameters handled. It wasn’t found a definite linearity between some carcass measurements, characteristics, and differences of some important environmental factors such as birth weight, milk suction time, age.